2018
DOI: 10.1590/rbz4720170252
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors affecting production of beekeeping farms and development of risk management strategies: A new approach

Abstract: The aim of this investigation was to determine risk factors affecting production of beekeeping farms in Igdir province of Turkey and to develop strategies in coping with these risks. Research was based on data collected through a questionnaire applied to 85 beekeeping farms registered to Igdir Beekeepers' Union according to exact counting method. Factor analysis was applied to collected data to identify risk factors and risk management strategies. Factor analysis was conducted under principle component extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
0
6
0
2
Order By: Relevance
“…Conclusions 09 Siqueira et al [19] The red propolis, collected in the region of Brejo Grande-SE, presents characteristics of identity and quality compatible with the parameters established by the Ministry of Agriculture and has proven effective against E. faecalis, being able, with more studies, to become a valuable endodontic treatment 10 Pimenta et al [20] The present study demonstrated that, although medications based on brown propolis with or without calcium hydroxide have limitations inherent to an in vitro study, they are effective against E. faecalis 11 Siqueira et al [21] The results of this study show that, similar to chlorhexidine, red propolis alcoholic extract has good fungistatic and fungicidal activity against most samples of Candida species. This antifungal activity may hold a promise for future applications as an alternative treatment for infections caused by these fungi.…”
Section: N°bibliographic Referencementioning
confidence: 80%
See 2 more Smart Citations
“…Conclusions 09 Siqueira et al [19] The red propolis, collected in the region of Brejo Grande-SE, presents characteristics of identity and quality compatible with the parameters established by the Ministry of Agriculture and has proven effective against E. faecalis, being able, with more studies, to become a valuable endodontic treatment 10 Pimenta et al [20] The present study demonstrated that, although medications based on brown propolis with or without calcium hydroxide have limitations inherent to an in vitro study, they are effective against E. faecalis 11 Siqueira et al [21] The results of this study show that, similar to chlorhexidine, red propolis alcoholic extract has good fungistatic and fungicidal activity against most samples of Candida species. This antifungal activity may hold a promise for future applications as an alternative treatment for infections caused by these fungi.…”
Section: N°bibliographic Referencementioning
confidence: 80%
“…The Management of beekeeping identifies measures against the specific risks in this activity is very important for increasing productivity, income, and production and promoting beekeeping [10]. In this context, a systematic bibliographical review was carried out in different electronic databases, through descriptors referring to beekeeping in Brazil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iqbal et al (2018) examined farmers' perceptions of risk sources in cotton production in Pakistan, finding that frequent changes to agricultural policies, farm equipment prices, and inefficiencies in farm cooperatives are primary constraints. Karadas and Birinci (2018) conducted a factor analysis to assess risk sources in bee farming that create financial risks, finding concern in the presence of biotic stressors and theft in Turkey. Thompson et al (2019) used a best-worst choice experiment among farmers to assess the importance of types of risk in large commercial U.S. farms, finding that production, market, and financial risks are of greater concern than are personal or legal risks.…”
Section: Sources Of Riskmentioning
confidence: 99%
“…However, an important finding of this research was that beekeeping is considered a dangerous business that forces beekeepers to have a second job. Karadas and Birinci (2018) state that determination of factors adversely influencing apiculture and developing risk management strategies that identify measures against restraining risk factors are very important for the increase of productivity, income and production and promotion of apiculture. According to the respondents, bees are very delicate, and in case of any diseases, they can die leaving the beekeepers without income.…”
Section: Overview Of Contributionmentioning
confidence: 99%